2015
DOI: 10.4049/jimmunol.1401319
|View full text |Cite
|
Sign up to set email alerts
|

Human β Defensin-3 Increases CD86 Expression on Monocytes by Activating the ATP-Gated Channel P2X7

Abstract: We previously showed that human beta defensin-3 (hBD-3), an epithelial cell derived antimicrobial peptide, mediates chemotaxis and activation of myeloid cells. Here, we provide evidence that hBD-3 induces the co-stimulatory molecule CD86 on primary human monocytes by a mechanism involving autocrine activation of ionotropic P2X7 receptors (P2X7R) by ATP. Incubation of monocytes with hBD-3 resulted in increased expression of both the CD80 and CD86 co-stimulatory molecules. Treatment of monocytes with a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…P2X7R signalling induces inflammation leading to differentiation of Th17 lymphocytes, which are involved in the pathogenesis and potential treatment of psoriasis ( Killeen et al, 2013 ). P2X7R play a role in shaping the inflammatory microenvironment in psoriasis ( Lioi et al, 2015 ). Strong P2X7R expression is confined to the basal layer cell membrane, while P2Y 1 R were expressed all through the psoriatic epidermis.…”
Section: Skin Diseasesmentioning
confidence: 99%
“…P2X7R signalling induces inflammation leading to differentiation of Th17 lymphocytes, which are involved in the pathogenesis and potential treatment of psoriasis ( Killeen et al, 2013 ). P2X7R play a role in shaping the inflammatory microenvironment in psoriasis ( Lioi et al, 2015 ). Strong P2X7R expression is confined to the basal layer cell membrane, while P2Y 1 R were expressed all through the psoriatic epidermis.…”
Section: Skin Diseasesmentioning
confidence: 99%
“…LPS, on the other hand, acts primarily via TLR‐4 which further transduces through MyD88 or TRIF (which does not require PI(4,5)P 2 ) to activate NF‐κB, implying that the role of PI(4,5)P 2 does not appear critical and, hence, are not affected by wortmannin, neomycin or staurosporine. PI(4,5)P 2 binding of HBD‐3 might also explain IL‐1β induction and co‐stimulatory marker expression via ATP‐gated channel P2X 7 which is directly regulated by PI(4,5)P 2 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBD‐3 induces proinflammatory cytokine release in monocytes, macrophages, and keratinocytes as well as promotes iDC and monocyte maturation by activating NF‐κB, possibly through CCR2/6‐PLC‐dependent and/or TLR‐1/2‐dependent pathways . HBD‐3 can also induce co‐stimulatory marker expression via activation of ATP‐gated P2X 7 channel . In contrast, it was later demonstrated that the HBD‐3‐induced NF‐κB activation was not inhibited by a G‐protein inhibitor pertussis toxin, a MyD88 inhibitor or TLR‐1 or TRIF inhibitor, suggesting a G‐coupled protein‐ and TLR‐independent mechanism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies suggested that intrathecal gp120 may lead to an activation of NF-κB within the spinal cord in exaggerated pain states (Ledeboer et al, 2005), and gp120 has been shown to promote tissue and cell injury by inducing NF-κB activation (Kapasi et al, 2006). Previous researchers have found that P2X 7 receptors play a vital role in regulating the function of microglia, and can be activated by adenosine 5'-triphosphate (ATP), thus releasing inflammatory cytokines to mediate chronic inflammatory responses in neurons, ultimately resulting in neurotoxicity (Feng et al, 2015;Lioi et al, 2015). The P2X 7 receptor, which is involved in inflammatory and immune responses and is closely associated with neurodegenerative diseases, may represent a new target for the prevention and treatment of ADC.…”
Section: Introductionmentioning
confidence: 99%